Talitrid orientation as bioindicator of shoreline stability: Protected headland-bays versus exposed extended beaches. (June 2015) - Scapini, F.; Gambineri, S.; Rossano, C.; ElGtari, M.; Fanini, L.; Nourisson, D.H.
Graphical abstract: Highlights: Talitrid populations can locally adapt their behaviour if beaches are stable. Headlands-bay beaches offer stable environment with limited sediment transport. Talitrids can hardly adapt to extended beaches with changing sedimentary transport. Seagrass-banquette positively affects talitrid adaptation to shoreline. Orientation, a quantifiable adaptation, is proposed as bioindicator of beach stability. Abstract: The behaviour of talitrids, being a local adaptation to beaches, is known to be related to environmental stability. The use of behavioural responses of resident populations as bioindicator of shoreline stability has been tested under various conditions, including after soft and hard engineering actions to stabilise eroded beaches. Port structures likely have impact on sediment longshore transportation and shoreline stability. The question was whether talitrid orientation behaviour could be proposed as bioindicator of impacts also for sandy bays of limited extension and highly used for recreation, such as those in the vicinity of touristic port structures. Orientation experiments were carried out on a set of sandy beaches of different extension and morphology, each of them in the vicinity of a touristic port, across the Mediterranean coasts. The protocol included field orientation tests of populations of talitrids, then analysed in terms of orientation precision seawards (considering sun compass orientation as the most locally adapted behavioural mechanism) in different seasons (before and after the touristic season) and times of day. The populations from more protected (either naturally or artificially) headland-bays showed a higher precision of orientation with respect to the shoreline direction than those from extended beaches, more subject to changes in longshore sedimentary transport as consequence of natural and human activities. The distance from the port and touristic pressure had no influence on talitrid orientation. An important stabilising factor for the sandy beach ecosystems, including talitrid populations and their behavioural adaptation, appeared to be the presence of seagrass banquette. The behavioural data point out that biotic information proceeding from local animal populations linked to beach sediments may complement sedimentology data and allow scaling the impacts occurring on a developed coastline. This becomes particularly relevant when considering interdisciplinary approaches to monitoring strategies.